Blockchain and the commons - Papadimitropoulos, Vangelis (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Recent years have seen a surge of interest in 'the commons' based on a simple yet radical idea: great improvements in production and management could be achieved by reducing barriers to knowledge exchange and power-sharing. Ranging from meadows, forests and parks to language, open source software (FLOSS and Blockchain) and 3D printers, the commons are distributed or common property resources/infrastructures which are self-managed by their user communities. While acknowledging the significant contributions that can be made through commons-based peer production, this book provides a critical examination of the commons with the aim of contributing to their long-term sustainability. In particular, the book examines the relation of Blockchain to the commons by illustrating the case study of the Commons Stack. Drawing on a range of interdisciplinary ideas and methodologies, the chapters argue that there are a number of economic and social barriers which are obstructing the wider reproduction of the commons. Problems with access to capital and training, the lack of entrepreneurial and managerial skills, and the absence of institutional support from governments, larger coops, and NGOs, are some of the external problems facing the commons today. Meanwhile, localism, gated communities, vested interests, atavism, traditionalism, ideology, conflict, neo-conservatism and techno-elitism represent some of the internal contradictions inherent in the commons. Through overcoming these contradictions, the ultimate goal is to transform capitalism into the postcapitalism of the commons: the creation of a social economy self-organised around the commons. This book provides vital reading for anyone interested in the commons from economics, techno-politics and across the social sciences. Vangelis Papadimitropoulos is a post doc researcher in the School of Political Sciences at Panteion University, Athens, Greece"--
Keywords: Cooperation; Blockchains (Databases) -- Economic aspects; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Economics / Theory